2020
DOI: 10.1590/1982-0216/20202258119
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of deaf patients with the health care

Abstract: Purpose: to investigate the satisfaction of deaf people in relation to the health services, to characterize the sample regarding sociodemographic, socioeconomic, and self-perception of deafness, and to verify if there is an association between satisfaction with care, communication, professionals, and self-perception of deafness. Methods: an observational, cross-sectional study conducted with a semi-structured questionnaire in 74 deaf adults. A descriptive analysis of the characterization of the sample and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…The findings of this study support earlier research addressing unsatisfactory communication with patients who are deaf [11][12][13]. The strategies and actions for improved deaf patient communication based on our own and prior research are listed in Table 4.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of this study support earlier research addressing unsatisfactory communication with patients who are deaf [11][12][13]. The strategies and actions for improved deaf patient communication based on our own and prior research are listed in Table 4.…”
Section: Discussionsupporting
confidence: 84%
“…The present research, it must be said, was conducted at two support institutions for the community of deaf people, not directly related to health services. However, a study conducted 13 with deaf people who received care in both the public and private health networks verified that both groups were not satisfied with the medical care. They reported that the means of communication used by the professionals and the presence of an interpreter were not effective and that strategies would need to be implemented to ensure these population's accessibility to health and its comprehensiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected with a recently published semi-structured questionnaire made up of three parts 13 . The said study investigated the satisfaction of deaf users with the care received at health services, based on data from the first and second parts of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Há estudos que demonstram que as crianças surdas inseridas em ambiente bilíngue desenvolveram com excelência as habilidades auditivas e linguísticas, sendo que a Libras auxiliou o desenvolvimento da linguagem 22,23 . No caso dos adultos, estudos sobre a satisfação do surdo em relação aos atendimentos da área de saúde indicaram que a maioria dos participantes eram bilíngues, indicando a importância da Libras e da língua oral [25][26][27][28] . Nesse contexto, possivelmente, a Libras representa importante contribuição para o desenvolvimento linguístico na oralidade desses estudantes surdos.…”
Section: Discussionunclassified